Impact of Covid-19 on Routine Activities at the Sholahuddin Mosque University of Palangka Raya, Indonesia - Syamhudian Noor; Ahmad Saefulloh (The Journal of Society and Media, 2022)
The impact of COVID-19 pandemic been felt Muslims, especially mosque administrators who manage places of worship. PSBB in the city Palangka Raya has restricted many activities, one which is Friday prayers in congregation at the mosque. The result of an agreement said that Friday prayers in congregation were replaced with noon prayers at home. This condition makes the financial income the mosque to be reduced and experience financial depletion. The purpose study was to see the impact of covid-19 on the decline in financial income of the mosque at the Sholahuddin campus, as well as how the management efforts to overcome the operational costs of the mosque. The research method is descriptive analysis phenomenological approach. Data collection done by interviewing. The data collection technique used purposive sampling. The results obtained of eliminating routine mosque program were reduction in decline mosques, reduction takmir mosque, and delay in the physical construction mosque.